2021
DOI: 10.1002/anie.202108201
|View full text |Cite
|
Sign up to set email alerts
|

New Mechanistic and Reaction Pathway Insights for Oxidative Coupling of Methane (OCM) over Supported Na2WO4/SiO2 Catalysts

Abstract: The complex structure of the catalytic active phase, and surface‐gas reaction networks have hindered understanding of the oxidative coupling of methane (OCM) reaction mechanism by supported Na2WO4/SiO2 catalysts. The present study demonstrates, with the aid of in situ Raman spectroscopy and chemical probe (H2‐TPR, TAP and steady‐state kinetics) experiments, that the long speculated crystalline Na2WO4 active phase is unstable and melts under OCM reaction conditions, partially transforming to thermally stable su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 46 publications
0
61
0
Order By: Relevance
“…18,19 Wachs and co-workers also differentiate between two kinds of active oxygen species, namely, atomic oxygen species associated with surface Na-WO x sites and molecular O 2 dissolved in the molten Na 2 WO 4 phase. 16,17 It should, however, be mentioned that dissolved O 2 was not directly detected. Its existence was assumed as gas-phase O 2 had been observed upon 13 CH 4 pulsing over the 5Na 2 WO 4 /SiO 2 catalyst at 800 °C in the TAP reactor under high vacuum conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…18,19 Wachs and co-workers also differentiate between two kinds of active oxygen species, namely, atomic oxygen species associated with surface Na-WO x sites and molecular O 2 dissolved in the molten Na 2 WO 4 phase. 16,17 It should, however, be mentioned that dissolved O 2 was not directly detected. Its existence was assumed as gas-phase O 2 had been observed upon 13 CH 4 pulsing over the 5Na 2 WO 4 /SiO 2 catalyst at 800 °C in the TAP reactor under high vacuum conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 22 Further evidence of the dispersed phase Na–WO 4 surface sites being the critical OCM active sites was provided in recent experimental studies 48,72 where temporal analysis of products (TAP) reactor studies in conjunction with steady-state OCM reaction studies of Na 2 WO 4 /SiO 2 catalysts (without Mn-oxide) demonstrated that the dispersed surface Na–WO 4 sites were responsible for selectively activating CH 4 to yield C 2 and CO products, while molten Na 2 WO 4 phase was found to be mainly responsible for the over-oxidation of CH 4 to CO 2 , and oxidative dehydrogenation of C 2 H 6 to C 2 H 4 . 72 Likewise, Mn-containing phases including MnO x surface oligomers, MnWO 4 and Mn–WO 3 nanoparticles in Mn–Na–WO x /SiO 2 tri-metal oxide model OCM catalyst were found to be primarily spectating during OCM under differential reaction conditions and when such Mn phases are present in small populations. 48 An older model study had previously shown that Na-coordinated WO 4 surface sites were more selective but slightly less active than Mn-coordinated WO x and uncoordinated WO x sites during OCM in a series of model bi-metal oxide OCM catalysts.…”
Section: Resultsmentioning
confidence: 94%
“…Recent state-of-the-art understanding regarding the role of Mn-and Na-promoters in Mn 2 O 3 -Na 2 WO 4 /SiO 2 OCM catalysts puts chemical insights provided in the present work in perspective.It was recently shown via experimental CH 4 +O 2 temperature-programmed-surface-reaction of well-defined single site catalysts that Na 2 WO 4 surface sites could effectively and selectively activate CH 4 in absence of any Mn-promoter to form C 2 products, making the role of Mn-promoter unclear 22. Further evidence of the dispersed phase Na-WO 4 surface sites being the critical OCM active sites was provided in recent experimental studies48,72 where temporal analysis of products(TAP) reactor studies in conjunction with steady-state OCM reaction studies of Na 2 WO 4 /SiO 2 catalysts (without Mn-oxide) demonstrated that the dispersed surface Na-WO 4 sites were responsible for selectively activating CH 4 to yield C 2 and CO products, while molten Na 2 WO 4 phase was found to be mainly responsible for the over-oxidation of CH 4 to CO 2 , and oxidative dehydrogenation of C 2 H 6 to C 2 H 4 . 72 Likewise, Mn-containing phases including MnO x surface oligomers, MnWO 4 and Mn-WO 3 nanoparticles in Mn-Na-WO x /SiO 2 tri-metal oxide model OCMcatalyst were found to be primarily spectating during OCM under differential reaction conditions and when such Mn phases are present in small populations 48.…”
mentioning
confidence: 97%
“…While an oxidized surface is more relevant to actual OCM process conditions, the surface oxygen species are highly active and the subtleties of C−H bond activation are obscured by CO and CO 2 formation during methane pulse response experiments. 9,49 The surface oxygen is depleted but still sufficient for C−H bond activation while avoiding over-Scheme 2. Mechanism for Molecular Adsorption and Molecular Exchange oxidation of CH x surface intermediates.…”
Section: Methane Activationmentioning
confidence: 99%
“…This work, together with global kinetic data and operando structural characterization, indicated that surface Na−WO x sites are responsible for selectively activating CH 4 to C 2 species. 9 Regarding the role of Mn, it has been proposed that Mn increases the mobility of surface oxygen, acts as an oxygen donor to the WO 4 centers, or increases the availability of oxygen from the lattice of molten Na 2 WO 4 at reaction temperatures. 7 Werny et al suggested the important role of Mn in the transient release and storage of active sodium oxide species.…”
Section: Introductionmentioning
confidence: 99%